Exercises in psychological testing - Condon, Margaret E.; Hollis-Sawyer, Lisa A.; Thornton, George C. (Boston : Allyn and Bacon, 2002)
A workbook with tear-out pages to be used in a graduate or undergraduate course on psychological testing to provide students with hands-on experience in various aspects of test development and use. Among them are giving and scoring several kinds of tests, constructing measurement scales, computing
Keywords: Psychological tests -- Problems, exercises, etc